Expression and Assembly of Procoagulant Complexes by Human Pleural Mesothelial Cells - Kumar, Anuradha; Koenig, Kathleen B; Johnson, Alice R; Idell, Steven (Thrombosis and Haemostasis, 1994)
Many pleural diseases involve fibrin deposition within the pleural cavity, an event that necessarily involves the mesothelium. This study of human pleural mesothelial cells (HPMC) was designed to determine how the mesothelium initiates and sustains the coagulation process. We used functional assays for activation of both factor X and prothrombin to examine expression and assembly of procoagulant activity by human pleural mesothelial cells in culture. The rates of factor Xa and thrombin formation were calcium-dependent. The rate of factor Xa formation in the presence of added factor VII increased in a concentration-dependent manner, suggesting that tissue factor is the primary procoagulant associated with HPMC. The fact that direct binding of radioiodinated factor Vila to HPMC was specific, concentration-dependent and saturable confirms that tissue factor is expressed on the cell surface. The rate of thrombin formation increased with factor Xa concentration, and the rate was 5-, 6-fold higher in presence of added factor Va indicating that HPMC support expression of prothrombinase activity. Further, direct binding of radioiodinated factor Xa to HPMC was specific, concentration-dependent and saturable, confirming that the cells support the assembly of the prothrombinase complex.